Mapping the Sacred Landscape: Spatial Representation and Narrative in Panoramic Maps of Mount Wutai and Mount Putuo - Yiwei Pan (Religions, 2025)
In late imperial China, a type of painting known as “panoramic maps” (shengjing tu 聖境圖, literally “sacred realm maps”) depicted Buddhist sacred sites. Often surviving as woodblock prints, examples from Mount Wutai and Mount Putuo are particularly representative. Previous research has often viewed these images as pilgrimage guides or focused on the relationship between pictorial perspectives and actual geography. This study centers on panoramic maps of Mount Wutai and Mount Putuo, examining both vertical and horizontal layouts, to offer a preliminary understanding of this genre. This study argues that: (1) Unlike urban maps, panoramic maps emphasize significant monasteries and landscape features, incorporating local legends and historical narratives, thus possessing strong narrative qualities. (2) These images likely functioned as pilgrimage souvenirs. Diverging from practical roadmaps, their primary goal was not strict realism but rather to convey the site’s sacredness and associated information through landscape painting conventions, allowing viewers to perceive its sacredness. (3) The woodblock print medium facilitated affordable reproduction, accelerating the circulation of the sacred site’s significance among the populace and aiding in its promotion. This research contends that the panoramic maps primarily function as folk landscape paintings reflecting the sacred site, capable only of approximating the relative positions of features. The widespread adoption of late-period woodblock printing enabled the low-cost reproduction and dissemination of the sacredness inherent in these Buddhist landscapes, constructing idealized spatial representations shaped by religious belief and geomantic principles.